Niveles de Jugo de Naranja (Citrus Aurantium L.), como Antioxidante Natural en la Elaboracion de Tilapia Ahumada. - Cabrera Rodríguez, Carla Priscila (2012)
he present investigation was carried out in the experimental property “the María” of the State Technical University of Quevedo, in the Shop of Meat of the Ability of Cattle Sciences, the same one that is located in the km. 7 of the road Quevedo-The Connection, county of the Ríos, the geographical location is of 1º 62’ 30” of south latitude 79º 29’ 30” of latitude west and to a height 124 meters on the level of the sea. The investigation was taken effect among the months of October to December of the 2012. The study factors were levels of orange juice, as anti-rust natural in the elaboration of Tilapia (T0 = 0% of orange juice, T1 = 0.05% of orange juice, T2 = 0.10% of orange juice, T3 = 0.15% of orange juice). As general objective he/she settled down “to Elaborate Smoky Tilapia with different levels of orange juice like anti-rust natural.”, also, as specific objectives they thought about 1) to Determine the effect of the levels of orange juice, as anti-rust natural in the elaboration of smoky tilapia. 2) to establish the costs of production and their profitability. A design was used totally at random (DCA) with four treatments, six repetitions giving a total of 24 experimental units. For the comparison of the averages among the treatments the test was used from Tukey to 5% of probability. As study variables they thought about: Analysis bromatológico (Percentage of humidity, protein percentage, percentage of fat and percentage of ash), Analysis microbiológico (Aeróbiosmesófilos, total Coliformes), organoleptic Analysis (Color, Flavor, Scent and Texture). Being concluded after the field work and of the analysis and interpretation of data in; 1) The content of ash was influenced by the levels of orange juice which highlighted to the treatment T3 with 23.21%. 2) in the protein content bigger effect was achieved with the treatment T0 with 35,31% what indicates that the Tilapia is kind of a high value proteico. 3) the content of fat is conserved since by the present anti-oxidants in the orange juice results they were evidenced with 18,71% with the treatment T0. 4) in the the alone evaluated organoleptic variables in the variable scent to smoke and soft texture was the averages 3.73 and 3.58, respectively which were acceptable and pleasant for its consumption. 5) the treatment 1 reached the biggest net profits and profitability with $5.73 and 25.73% being an attractive business to undertake and to develop.